Oral Hemangiom with Multiple Phleboliths - Duran, Merve Hacer; Baybars, Sümeyye Coşgun (My University, 2023)
Hemangioma is a rare, non-reactive, benign vascular tumor, characterized by endothelial cell proliferations and results from vascular malformation. Hemangioma mostly occurs on head and neck skin and regresses spontaneously within 5-10 years in 50-90% of cases. However, oral lesions show less regression than skin lesions. The most commonly affected area is tongue and palatal mucosa, and rarely observed in jaw bones. Diagnosis is based on anamnesis and clinical features. Blanching of the hemangioma under pressure is characteristic clinical finding. Phlebolith is calcified thrombus in veins, venules and sinusoidal walls of hemangiomas. Head and neck phleboliths almost always indicate the soft tissue hemangioma. Phleboliths observed with hemangioma in head and neck region have distinctive appearance on panoramic radiographs. Cone-beam computed tomography provides useful information about location and distribution of phleboliths. In this case report, clinical and radiological features of oral hemangioma and many associated phleboliths are presented.
Keywords: Mikroskopi; Diş Hekimliği; Patoloji; Nörolojik Bilimler; Kulak; Burun; Boğaz; Sağlık Bilimleri ve Hizmetleri